O monitoramento climático e o alerta de desastres naturais na era da comunicação digital - Magnoni, Antonio Francisco [UNESP]; Magnoni Júnior, Lourenço; Figueiredo, Wellington dos Santos; Andreo, João Ricardo [UNESP] (My University, 2012)
This article presents considerations concerning the interaction between communication and digital platforms and applications developed to perform computerized climate monitoring and issue alerts about natural disasters. From work in the Center for Integrated Natural Disaster Alert (CIADEN), which processes meteorological data provided by Platform Monitoring, Analysis and Warning TerraMA2 designed by the National Institute for Space Research (INPE) to conduct monitoring and fi ring warning about climate risk environment, we propose the expansion of interactivity with the various possibilities of digital communication available today for signifi cant portion of society. On another front, the CIADEN has articulated teaching and research on climate monitoring and warning of natural disasters, weather, and geoprocessing environment, involving teachers and students both in school and in higher and technical.

O presente artigo traz considerações sobre a interatividade entre a comunicação digital e as plataformas e aplicativos informatizados desenvolvidos para realizar monitoramento climático e emitir alerta sobre desastres naturais. A partir de trabalho desenvolvido no Centro Integrado de Alerta de Desastres Naturais (CIADEN), que processa dados meteorológicos disponibilizados pela Plataforma de Monitoramento, Análise e Alerta TerraMA2 concebida pelo Instituto Nacional de Pesquisas Espaciais (INPE) para realizar monitoramento climático e disparar alerta sobre riscos ambientais, propomos a expansão da interatividade com as diversas possibilidades de comunicação digital disponíveis nos dias de hoje para signifi cativa parcela da sociedade. Numa outra frente, o CIADEN tem articulado atividades de ensino e pesquisa sobre monitoramento climático e alerta de desastres naturais, meteorologia, meio ambiente e geoprocessamento, envolvendo professores e alunos tanto no ensino médio e técnico quanto no superior.
Climate monitoring and alert of natural disasters in the era of digital communication
Keywords: Global warming; Climate change; Climate monitoring and alerting; Digital TV; Aquecimento global; Mudanças climáticas; Monitoramento e alerta climático; TV digital